Investigation of Efforts to Improve PDAM Services in Grobogan Regency - Hermawan, Eric; Kamar, Karnawi; Anggraini, Rizka Maulida; Nurakhim, Bambang; Judijanto, Loso (Universitas Dharma Wacana, 2024)
The quality of public services provided by the Regional Drinking Water Company (PDAM) in Grobogan Regency is the primary focus of this research. Guided by relevant theoretical frameworks, the study seeks to examine the current state of service delivery and identify opportunities for improvement. This research adopts a descriptive approach, which aims to provide a detailed depiction of phenomena as observed in the field.Data collection was conducted through a combination of observation, documentation, and interviews, allowing for a comprehensive understanding of the issues affecting service quality. The research was specifically carried out within the operational scope of the PDAM in Grobogan Regency, involving both internal processes and customer interactions.The findings reveal critical insights into the challenges and strengths of the PDAM’s service delivery. Key aspects explored include water quality, distribution efficiency, responsiveness to customer complaints, and the overall accessibility of services. While some areas demonstrate acceptable performance, significant gaps remain, particularly in meeting customer expectations and ensuring consistent satisfaction.This study emphasizes the importance of adopting customer-centric strategies to enhance service quality. Recommendations derived from the findings include improving infrastructure to ensure uninterrupted water supply, enhancing the responsiveness of complaint handling mechanisms, and implementing regular monitoring systems to address inefficiencies. Additionally, customer feedback should be systematically incorporated into decision-making processes to align services with community needs.By addressing these issues, the PDAM in Grobogan Regency can improve its public service quality, fostering greater trust and satisfaction among its customers. This research contributes valuable insights that support ongoing efforts to ensure access to reliable and high-quality drinking water services in the region